Community conservation and remote sensing of the desert-adapted lions in northwest Namibia - Heydinger, John (Frontiers in Ecology and Evolution, 2023)
Community-based conservation of the desert-adapted lions takes place within the semi-arid and arid environments of northwest Namibia. This area is primarily designated as communal conservancies, a form of community-based natural resource management (CBNRM). The article describes the activities of the Lion Rangers program, a CBNRM organization, emphasizing how the use of remote sensing techniques, including the Spatial Analysis and Report Tools (SMART) software and mobile-app, GPS/satellite collars, and trail cameras, contribute to lion monitoring and limiting human–lion conflict (HLC). Remote sensing data are being integrated with historical and sociological research, with applicable lessons for lion conservation and conservation of other problem-causing species.